Undercover kindness : saying yes to love, no to fear, and embracing the life-changing power of ordinary generosity - Darts, Jimmy; Blaine, Jamie (Convergent Books, 2025)
Jimmy Darts is convinced that the most fun we can have is to spread joy and kindness with no inhibition. He travels to thrift shops, laundromats, street corners, and grocery stores, looking for good Samaritans willing to help a down-on-his-luck stranger--and rewarding them extravagantly when they say yes. "Most of these people have been paying it forward their whole life," Darts writes, "but no one's noticed. This is their moment. God notices. And I want to let them know." In Undercover Kindness, Darts takes us behind the scenes of his unconventional life--one rooted in friendship with God, and a bold faith that fuels every act of generosity. From blessing strangers to crowdsourcing a helping hand, having adventures, making friends, and learning that the world is a kinder place than we generally believe, Jimmy shows that living by faith isn't just powerful--it's wildly fun. Undercover Kindness is just as unconventional as Jimmy Darts himself. With a mix of unforgettable stories, thoughtful reflections, and revelations that go beyond the vignettes shown in his videos, this book will help readers reignite their faith, rekindle their hope in humanity, and discover that a life of generosity can be fun, silly, unexpected, and poignant all at once.